APOE Gene Polymorphism and Risk of Coronary Stenosis in Pakistani Population. (26th March 2015) - Cheema, Asma Naseer; Bhatti, Attya; Wang, Xingbin; Ali, Jabar; Bamne, Mikhil N.; Demirci, F. Yesim; Kamboh, M. Ilyas
Abstract : Genetic variation in lipid regulatory genes, particularly APOE, significantly influences the risk of coronary artery disease (CAD). This study aimed to assess the association between APOE polymorphism and angiographically assessed coronary stenosis in Pakistani population. A total of 695 subjects (22.3% female, mean age = 54 ± 11 years) presenting with chest pain were enrolled after obtaining written informed consent. CAD stenosis/extent was assessed by angiography. Patients were classified as having severe stenosis (≥70%), moderate stenosis (30–69%), and mild stenosis (<30%). CAD patients with ≥70% stenosis (n = 491 ) were further categorized based on possessing one, two, or three vessel diseases to assess the disease extent. Genomic DNA from leukocytes was isolated with DNA purification kit (Qiagen) and APOE polymorphisms (E2/E3/E4) were determined using TaqMan assays. Six hundred and seventy-two of 695 subjects were successfully genotyped. The frequency of APOE∗ 4 carriers (3/4 and 4/4 genotypes) was significantly higher in severe stenosis group (≥70%) as compared to mild group (<30%) (22.8% versus 13.01%; P = 0.01 ). In multiple regression, the odds ratio for APOE∗ 4 carriers to develop ≥70% stenosis was 2.16 (95% CI: 1.29–3.79; P < 0.005 ). In conclusion, the presence of APOE∗ 4 allele is a significant risk factor to develop severe coronary stenosis (>70%) among Pakistanis.